Studies on Extraction of Flavonoids from the Peel of Pisum Sativum - Drishti Dhall; Ishika Gupta; Surya Prakash D.V. (International Journal of Biochemistry and Biomolecule Research, 2023)
Pisumsativum is commonly known as Pea plant and belongs to Fabaceae family. It is an herbaceous annual plant. Pea pods not only yield an adequate quality of dietary fibre but provide a substantial amount of proteins, sugars, and minerals. Globally, significant quantities of pea residue are generated, an enormous amount of which is used as animal feed. The pea pods consist of an appreciable amount of polyphenols, including phenolic acids such as 5-caffeoylquinic acid and flavanols like catechin and epicatechin. In this experiment, qualitative, quantitative and purification of phytochemicals are studied. In qualitative analysis, saponins, terpenoids, flavonoids and quinines are present based on observation of colour. In quantitative analysis, water extract and ethanolic extracts showed best result of quercetin and kaempferol and their concentrations were found to be 14.0 µg/ml and 11.5 µg/ml. In purification process, quercetin(water extract) and kaempferol(ethanolic extract) concentrations were found to be 17.0 µg/ml and 12.5 µg/ml.
Keywords: Extraction; Pisumsativum; kaempferol; purification; quercetin